Psychological Obstacles to the Formation of Loyalty of Employees of the Penitentiary System to Professional-Service Groups - Gornostaev, S.V. (Psihologiâ i pravo, 2023)
The article examines the factors that prevent the formation of loyalty of employees of penitentiary system to professional-service groups of their affiliation. The position is argued that alongside with absence of factors of formation of loyalty, there are specific socially-psychological obstacles for formation of loyalty to professional-service groups. Such obstacles were identified based on the analysis of empirical data (N=2786, respondents - men and the women engaging various positions in establishments and territorial units of Federal Penitentiary Service of Russia of 76 subjects of the Russian Federation; methods - The «Method of color metaphors», the questionnaire «Subjective assessment of integration»). In relation to large formal groups (like ministry) such an obstacle is the lack of experience of joint activities and emotional experiences in the group. At the level of large contact groups (organizations), the most significant factors preventing loyalty are the lack of exclusivity and value of the group, obvious differences in the normative and value orientations of their members. The main factor hindering loyalty to small contact groups in the professional and service sphere is the ignoring or rejection of a member of the group by its other members. В статье с учетом ранее проведенных исследований рассмотрены факторы, препятствующие формированию лояльности сотрудников уголовно-исполнительной системы профессионально-служебным группам принадлежности. Аргументируется позиция, что наряду с отсутствием факторов формирования лояльности имеются специфические социально-психологические препятствия для формирования лояльности профессионально-служебным группам. Такие препятствия выявлены на основе анализа эмпирических данных (N=2786, респонденты - мужчины и женщины, занимающие различные должности в учреждениях и территориальных органах ФСИН России 76 субъектов Российской Федерации; методы: «Методика цветовых метафор», анкета «Субъективная оценка интегрированности»). В отношении больших формальных групп (ведомств) таким препятствием является отсутствие опыта совместной деятельности и эмоциональных переживаний в составе группы. На уровне больших контактных групп (организаций) наиболее значимыми факторами, препятствующими лояльности, являются отсутствие эксклюзивности и ценности группы, очевидные различия в нормативно-ценностных ориентациях их членов. Главным фактором, препятствующим лояльности малым контактным группам в профессионально-служебной сфере, является игнорирование или отвержение члена группы другими ее членами. Отрицание служащим наличия у группы привлекательных для него ресурсов является наиболее универсальным фактором, препятствующим формированию лояльности в отношении профессионально-служебных групп всех типов.